The Disparity in Transit Travel Time between Koreans and Japanese in 1930s Colonial Seoul - Youngjoon Kim; Jinhyung Lee; Junghwan Kim; Naoto Nakajima (Findings)
Transportation is a key element to understanding the socio-spatial structure of colonial cities and the lives of individuals living under colonial governance. This study investigates the disparity in transit-based travel time between colonial rulers (Japanese) and subjects (Koreans) in Colonial Seoul (*Keijo*) in 1936 using modern GIS and open-source transport analysis tools. Findings suggest a significant disparity in travel time to a major urban facility (i.e., City Hall) between the two population groups of the largest colonial city in the Korean peninsula.